Propuesta de un material descartable como aislante térmico: aplicación a un digestor anaeróbico enterrado - Morales, Martín Alberto (2016)
An alternative for use as thermal insulation is presented in this paper. This was built with disposable materials such as wood chips and disposable PET bottles. This isolation was subjected to a study to assess the heat diffusion inside and determine the thermal diffusivity after the application of the heat equation. Then this insulation was used to isolate an anaerobic digester buried. Given the low cost of insulation positively affects the final cost of the digester. The thermal diffusivity calculated predicts that the proposed insulation help maintain a suitable temperature inside the digester.